2017
DOI: 10.1002/jcb.25824
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Pro‐Inflammatory Cytokine IL‐1β on Butyrate Oxidation in Colorectal Cancer Cells

Abstract: Cancer, in part, is driven, by alterations in cellular metabolism that promote cell survival and cell proliferation. Identifying factors that influence this shift in cellular metabolism in cancer cells is important. Interleukin-1β (IL-1β) is a pro-inflammatory cytokine that has been reported to be elevated in colorectal cancer patients. While much is known toward the effect of dietary nutrients on regulating inflammation and the inflammatory response, which includes cytokines such as IL-1β, far less is underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Previous studies demonstrated that mutations in the IL-6 gene may increase the risk for AD [45,46]. IL-1β activates NF-κB and p38 signaling pathways to further worsen neuronal cell dysfunction [47]. Therefore, inhibiting the expression of RAGE and RAGE/NF-κB mediated neuroinflammatory responses may be an effective therapeutic strategy for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that mutations in the IL-6 gene may increase the risk for AD [45,46]. IL-1β activates NF-κB and p38 signaling pathways to further worsen neuronal cell dysfunction [47]. Therefore, inhibiting the expression of RAGE and RAGE/NF-κB mediated neuroinflammatory responses may be an effective therapeutic strategy for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-promoting inflammation is now an emerging hallmark of cancer, which sounds unanticipated and paradoxical but proved to be virtual in its tumorigenesis journey. Succinate is widely accepted as an inflammatory signal and induces interleukin-1β (IL-1β) through HIF-1α [ 89 ] while IL-1β has been demonstrated to be elevated in colorectal cancer [ 90 ], oral cancer [ 91 ] and colon cancer [ 92 ]. Taken together, accumulation of succinate in the tumor microenvironment finally enhances the tumor-associated inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups over the last two decades have also observed elevated inflammatory cytokine and chemokine profiles in the serum of patients with solid cancers. Significantly elevated expression of IL1-β, IL-6, IL-8, IL-10, IL-17, TNF-α, TGF-β, IFNγ, and C-X-C motif chemokine ligand 1 (CXCL1) has been seen in colorectal cancer and other solid cancers like lung cancer (51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%